2015
DOI: 10.5194/acp-15-799-2015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of HONO budgets for two measurement heights at a field station within the boreal forest in Finland

Abstract: Abstract. Atmospheric concentrations of nitrous acid (HONO), one of the major precursors of the hydroxyl radical (OH) in the troposphere, significantly exceed the values predicted by the assumption of a photostationary state (PSS) during daytime. Therefore, additional sources of HONO were intensively investigated in the last decades. This study presents budget calculations of HONO based on simultaneous measurements of all relevant species, including HONO and OH at two different measurement heights, i.e. 1 m ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 69 publications
7
74
0
Order By: Relevance
“…These results stimulated laboratory investigations on potential HONO precursors from which the most frequently discussed mechanisms are (i) the photosensitized reduction of nitrogen dioxide (NO 2 ) by organic material, e.g. humic acids (George et al, 2005;Stemmler et al, 2006;2007, Sosedova et al, 2011Han et al, 2016), (ii) the photolysis of adsorbed nitric acid (Zhou et al, , 2011Laufs and Kleffmann, 2016), (iii) biogenic production of nitrite in soil (Su et al, 2011;Ostwald et al, 2013;Maljanen et al, 2013;Oswald et al, 2015;Scharko et al, 2015;Weber, 2015) and (iv) release of adsorbed HONO from soil surfaces after deposition of strong acids (VandenBoer et al, 2013(VandenBoer et al, , 2014(VandenBoer et al, , 2015Donaldson et al, 2014). Another discussed source, the reaction of excited gaseous NO 2 with water (Li et al, 2008), is of minor importance as demonstrated by laboratory (Crowley and Carl, 1997;Carr et al, 2009;Amedro et al, 2011) and modelling studies (Sörgel et al, 2011b;Czader et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results stimulated laboratory investigations on potential HONO precursors from which the most frequently discussed mechanisms are (i) the photosensitized reduction of nitrogen dioxide (NO 2 ) by organic material, e.g. humic acids (George et al, 2005;Stemmler et al, 2006;2007, Sosedova et al, 2011Han et al, 2016), (ii) the photolysis of adsorbed nitric acid (Zhou et al, , 2011Laufs and Kleffmann, 2016), (iii) biogenic production of nitrite in soil (Su et al, 2011;Ostwald et al, 2013;Maljanen et al, 2013;Oswald et al, 2015;Scharko et al, 2015;Weber, 2015) and (iv) release of adsorbed HONO from soil surfaces after deposition of strong acids (VandenBoer et al, 2013(VandenBoer et al, , 2014(VandenBoer et al, , 2015Donaldson et al, 2014). Another discussed source, the reaction of excited gaseous NO 2 with water (Li et al, 2008), is of minor importance as demonstrated by laboratory (Crowley and Carl, 1997;Carr et al, 2009;Amedro et al, 2011) and modelling studies (Sörgel et al, 2011b;Czader et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…During the last decades, many field measurement campaigns have reported unusually high nitrous acid (HONO) concentrations during daytime for remote (Zhou et al, 2002;Acker et al, 2006a;Sörgel et al, 2011a;Villena et al, 2011;Oswald et al, 2015;Meusel et al, 2016), semi-urban (Neftel et al, 1996;Staffelbach et al, 1997;Kleffmann et al, 2005;Su et al, 2008;Li et al, 2012;Yang et al, 2014) and urban regions (Kleffmann et al, 2002, Ren et al, 2003Acker et al, 2006b;Elshorbany et al, 2009Elshorbany et al, , 2010Hou et al, 2016;Lee et al, 2016). These results stimulated laboratory investigations on potential HONO precursors from which the most frequently discussed mechanisms are (i) the photosensitized reduction of nitrogen dioxide (NO 2 ) by organic material, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This can be ruled out in this study, as pure air (no NO 2 ) was used to purge the chambers and no light was applied. While in Cyprus the observed soil emissions can explain high amounts of atmospheric HONO, other studies excluded soil emission as a dominant source (Oswald et al, 2015;Laufs et al, 2017). Oswald et al (2015) studied soil samples from a boreal forest in Finland and observed HONO emissions below the detection limit.…”
Section: Comparison Of Soil Emissions and Observed Missing Sourcementioning
confidence: 99%
“…While in Cyprus the observed soil emissions can explain high amounts of atmospheric HONO, other studies excluded soil emission as a dominant source (Oswald et al, 2015;Laufs et al, 2017). Oswald et al (2015) studied soil samples from a boreal forest in Finland and observed HONO emissions below the detection limit. However, those samples had very low nutrient contents and were highly acidic (pH ≈ 3), for which microbial activity is supposed to be low (Fierer and Jackson, 2006;Persson and Wirén, 1995;Ste-Marie and Pare, 1999;Šimek and Cooper, 2002).…”
Section: Comparison Of Soil Emissions and Observed Missing Sourcementioning
confidence: 99%
See 1 more Smart Citation